Meat yield of the mangrove crab, Ucides cordatus (Linnaeus, 1763) (Crustacea, Brachyura, Ucididae) - Pinheiro, Marcelo Antonio Amaro [UNESP]; Souza, Caroline Araújo de; Borba, Hirasilva [UNESP] (Inst Pesca, 2015)
Specimens of Ucides cordatus were captured from September 1998 to September 2000 in mangroves from Iguape, SP, Brazil (24 degrees 41'25 ''S - 47 degrees 27'48 ''W) and analyzed by sex, biological period (reproductive, October to March; and non-reproductive, from April to September) and size. The meat yield of each corporal structure, and the residuals were quantified. Each crab was measured (carapace width) with a vernier caliper (0.05 mm) and their corporal structures weighed with an analytic scale (0.0001 g). Biometric variables were previously tested (normality and homoscedasticity) with indication of a statistical parametric procedure (ANOVA) at 5% significance level. Males had higher wet weight than females, the same occurring when their corporal structures were compared (p<0.05). The meat yield in males was of 25.4%, a little above than what was registered in females (21.1%); meat yield hierarchy among corporal structures was very similar between sexes and biological periods, but differing in relation to chelipeds, which were bigger in males. During the reproductive period males had a bigger meat yield due to their size when compared to males of non-reproductive period, as well as with females independently of their biological period. The expressive meat yield in males can be explained by the positive allometric growth of the chelipeds after puberty molt when this structure grows proportionally more than the body itself, accounting for 40% of the total wet weight in this gender.

Espécimes de Ucides cordatus foram capturados de setembro de 1998 a setembro de 2000, nos manguezais de Iguape, SP, Brasil (24º41’25''S – 47º27’48''O) e analisados por sexo, período biológico (reprodutivo: outubro a março; e não reprodutivo: abril a setembro) e tamanho. O rendimento de carne de cada estrutura corporal e os resíduos foram quantificados. Cada caranguejo foi medido (largura da carapaça) com um paquímetro (0,05 mm) e suas estruturas corporais pesadas com uma balança analítica (0,0001 g). As variáveis biométricas foram previamente testadas (normalidade e homocedasticidade) com indicação de um procedimento estatístico paramétrico (ANOVA) ao nível de 5% de significância. Os machos apresentaram maior peso úmido do que as fêmeas, o mesmo ocorrendo quando suas estruturas corporais foram comparadas (p<0,05). O rendimento de carne nos machos foi de 25,4%, pouco acima daquele registrado nas fêmeas (21,1%), sendo a hierarquia de rendimento de carne entre as estruturas corporais muito similares entre os sexos e os períodos biológicos, porém diferindo em relação ao peso dos quelípodos, que foram maiores nos machos. Durante o período reprodutivo, os machos apresentaram um maior rendimento de carne de acordo com seu tamanho em relação aos machos do período não reprodutivo, bem como com as fêmeas, independentemente do seu período biológico. O rendimento de carne, mais expressivo nos machos, pode ser explicado pelo crescimento alométrico positivo de seus quelípodos logo após a muda da puberdade, quando esta estrutura cresce proporcionalmente mais do que o próprio corpo, representando 40% do peso úmido total neste gênero.
Rendimento de carne do caranguejo-uçá, Ucides cordatus (Linnaeus, 1763) (Crustacea, Brachyura, Ucididae)
Keywords: Biometry; Crab; Fishery resource; Meat extraction; Morphology; Reproduction; Biometria; Caranguejo; Extração de carne; Morfologia; Recurso pesqueiro; Reprodução